A Model For The Origin Of Hydrophobic Force - R. Pazhianur (Society for Mining, Metallurgy & Exploration, 2003)
Many investigators conducted surface force measurements between hydrophobic surfaces in water, and observed attractive force that was substantially stronger than the van der Waals attractive force. The excess force was appropriately referred to as “hydrophobic force”, for which many different theories have been put forth by numerous investigators. In an earlier publication (Yoon and Ravishankar, 1996), it was suggested that the hydrophobic force maybe due to the interaction between the large dipoles created by the surfactants adsorbing on solid surfaces in patches (or domains). In the present work, a mathematical model has been developed to further elaborate the theory.